Developing Public Health Students' Strategic Skills Through Authorship Training. (June 2023) - August, Ella; Zelner, Sarah; Zelner, Jon; Anderson, Olivia S.
Collaborative writing skills are essential for public health professionals to carry out their work in a variety of settings, however, these strategic skills are not being taught comprehensively in public health schools and programs. In this paper, we argue that instructors should train public health students on a range of issues related to authorship, and we frame this training as a way of creating equitable opportunities for students to develop key professional skills. We conclude with specific recommendations and resources to support this training.